AI LIBRA VIRTUAL LIBRARY ASSISTANT: INTELLECTUALIZATION OF THE NU LIBRARY WEB-PORTAL USER INTERFACE ON THE BASIS OF AI APPLICATIONS - Toktassyn, Altay; Unaspekov, Timur; Slamkhan, Sat; Gabdullin, Sirazh; Kenzhebayev, Alisher (Nazarbayev University School of Engineering and Digital Sciences, 2024)
This project is made to improve the existing library system of Nazarbayev University. Dr. Askar Boranbayev and Dr. Piotr Lapo offered us to take on this project. Our solution strives to make the NU library system convenient and efficient for students and faculty members. Our goal is to improve the user experience when working with the library system, make it more interactive, and also reduce the time it takes to find a book that matches the user’s interests. Former NU Library Director, Dr. Piotr Lapo, together with our professor Dr. Askar Boranbayev, advised us to use artificial intelligence based on their experience. Our team, together with our advisors, came to a unified implementation. We have introduced a virtual assistant. Firstly, it performs the function of voice announcements on the NU library website, using the Google Cloud Platform. Secondly, our assistant answers arbitrary questions from users regarding the library, based on the "spaCy" model. We also developed our own model to improve the skill of working with Natural Language Processing tasks. But in the end, we came to the conclusion that spaCy works better. We used a database of answers to frequently asked questions from the NU library website to train our model. Thirdly, we implemented a smart book recommendation system so that the user can get information about the book based on his interests and other users' reviews. Our solution works in the format of a Backend web application, which in the future will be integrated with the NU library system. But while we have not integrated with the NU library system, we have written our own Frontend application for simulation in order to fully test it and demonstrate the results. Frontend is written in React. The backend is written using Fast API. PostgreSQL was used to manage the database. It should be noted that our team led by Dr. Askar Boranbayev presented this project at the International Scientific and Practical Conference "Industrial Development: Technologies for People and Services in the Era of Innovation".
Keywords: Type of access: Open access